Microwave-assisted deposition of a highly active cobalt catalyst on mesoporous silica for photochemical CO2 reduction. Issue 32 (8th June 2017) - Fenton, Thomas; Gillingham, Samantha; Jin, Tong; Li, Gonghu
Abstract : Uniform Co(iii ) sites were obtained on the silica surfaces. Thermal treatment under vacuum resulted in significant changes in the properties of the Co(iii ) sites. Abstract : Coupling with robust surfaces is a promising approach to improve the stability and recyclability of highly active molecular catalysts. This study builds on our prior success to deposit a Co(iii ) cyclam complex, where cyclam is 1, 4, 8, 11-tetraazacyclotetradecane, on mesoporous silica via a microwave-assisted process. The Co(iii ) complex was successfully deposited on the silica surface through reacting with silanol groups in the silica mesopores. The resulting surface Co(iii ) catalyst was characterized by different techniques and tested in photochemical CO2 reduction in the presence of p -terphenyl as a photosensitizer. The synthesized Co(iii ) catalyst showed significantly higher activity and selectivity than the unbound Co(iii ) cyclam complex and a surface Co(iii ) catalyst prepared by other methods. Microwave-assisted heating was found to be essential for the deposition of uniform Co(iii ) sites in the silica mesopores, which likely accounts for the superior activity and selectivity of the synthesized surface Co(iii ) catalyst.